The pulmonary collectins, SP-A and SP-D, orchestrate innate immunity in the lung - Francis X. McCormack; Jeffrey A. Whitsett (2002)
Innate defenses in the lungEach day respiration moves 15,000 liters of air containing hundreds of microorganisms over the 150-m 2 respiratory epithelial surface.Most inhaled microbes are trapped on the mucus layer coating the nasal epithelium and upper respiratory tract and are transported by ciliary motion to the pharynx, where they are swallowed.Organisms that reach the alveolar compartment are deposited on the alveolar lining layer (ALL), a thin aqueous film containing pulmonary surfactant that lines the gas-exchanging surface of the pulmonary epithelium.After "touchdown," complex offensive and defensive strategies are initiated by both the invader and the host.Sensing of the physiologic body temperature and the pH and ionic strength of the ALL by the organism triggers a program of gene expression designed to optimize survival under adverse conditions.These include upregulation of microbial genes required for proliferation and host evasion and downregulation of genes that regulate less necessary functions.The lung response to this threat is coordinated by the pulmonary epithelium and alveolar macrophages, which release cytokines and chemokines to recruit additional inflammatory cells to the airspace.However, a single organism capable of dividing every 20 minutes will give rise to a population of millions within hours, so control of proliferation must begin well before reinforcements arrive.For the naive host, the primary antimicrobial defenses in the ALL are the resident alveolar macrophages and protein components of the innate immune system, including the cell wall-degrading enzyme lysozyme, the iron-chelating protein lactoferrin, and specific membrane-permeabilizing members of the defensin, cathelicidin, and pentraxin families.Macrophages are activated by innate immune receptors such as CD14, which detect LPS, peptidoglycan, and other molecules displayed on the surface of microorganisms.Phagocytosis is triggered by pattern recognition receptors on the surface of the phagocyte, including the mannose receptor and the macrophage scavenger receptor, which identify signature carbohydrate structures on microbial surfaces.If the microbe has been previously encountered, recognition may also proceed through opsonization by specific antibody and Fc receptor-dependent uptake.These events result in extracellular microbial incapacitation and internalization into activated phagolysosomes, which kill the organism through exposure to lethal reactive oxygen species and lytic enzymes.